Adhesion and adhesives technology an introduction - Pocius, Alphonsus V. (Hanser Publications, 2012)
This book describes, in clear understandable language, the three main disciplines of adhesion technology: 1) mechanics of the adhesive bond, 2) chemistry of adhesives, and 3) surface science. Some knowledge of physical and organic chemistry is assumed, but no familiarity with the science of adhesion is required. The emphasis is on understanding adhesion, how surfaces can be prepared and modified, and how adhesives can be formulated to perform a given task. Throughout the book, the author provides a broad view of the field, with a consistent style that leads the reader from one step to the next in gaining an understanding of the science.
Keywords: Adhesion.; Adhesives.; Chemistry, Physical and theoretical.; elektronické knihy; electronic books